1998
DOI: 10.1007/bf02237385
|View full text |Cite
|
Sign up to set email alerts
|

Indication for using high ligation of the inferior mesenteric artery in rectal cancer surgery

Abstract: Although the five-year survival rate in patients with inferior mesenteric artery root nodal metastases was lower than in those without metastases, inferior mesenteric artery root nodal dissection should be performed after high ligation of the inferior mesenteric artery for patients with pT3 and pT4 cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
1
7

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 13 publications
1
31
1
7
Order By: Relevance
“…In a retrospective analysis of 198 cases of rectal cancer, metastases at the root of the IMA were found in 8.6% of the patients [39]. None of the 46 patients with pT1 or pT2 tumours presented IMA root nodal metastases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a retrospective analysis of 198 cases of rectal cancer, metastases at the root of the IMA were found in 8.6% of the patients [39]. None of the 46 patients with pT1 or pT2 tumours presented IMA root nodal metastases.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the fact that approximately one fifth of the patients experience significant blood flow reduction after IMA clamping, ischaemia-related anastomotic complications are encountered in around 5% of the cases, mostly elderly male patients [48]. Furthermore, a study comparing tissue oxygenation proximal to the colonic resection margin demonstrated that the marginal artery provides an adequate vascular supply to the transverse and descending colon [49], thus explaining the low anastomotic leak rates reported after high IMA ligation [39, 45, 46, 50]. Although the superior hypogastric nerves are at risk, ligation of the IMA at its origin is the safest option in order to avoid damage to the autonomic nerves [51, 52], which permits preservation of sexual and urinary functions in the great majority of the patients [35, 36, 53].…”
Section: Discussionmentioning
confidence: 99%
“…21 Moreover, the incidence of IMA lymph node metastasis was 4.79% in our study and was reported in previous studies to be low, ranging from 0.3% to 8.6%. 16,20,22,23 This low incidence could also be one of the reasons that we and others could not demonstrate a survival benefit. Taken together, there is no conclusive evidence to support a survival benefit among patients who undergo removal of IMA lymph node by high ligation.…”
Section: Discussionmentioning
confidence: 67%
“…A avaliação do perfi l qualitativo dos LN tem assumido importância crescente. Nesse contexto, o estudo do LN sentinela (6,10) (LN que recebe drenagem linfática diretamente da lesão primária), do tamanho dos LN (10) e das metástases nos LN (26,32) , da localização dos LN em relação à topografi a da lesão (8) , à proximidade do tumor (11) e de tronco vascular específi co (16) têm sido avaliados em relação ao prognóstico. O uso da imunoistoquímica mostrou-se método efi ciente na detecção de micrometástases (metástases menores que 2 mm) (6) , com impacto no estádio e no prognóstico dos pacientes (6,7,12) .…”
Section: Introductionunclassified